Selic rate variation and investors in variable income: analysis with B3 data - Cesar de Oliveira , Edenis; Amorim Jacomassi , Guilherme (Seven Editora, 2023)
The study aimed to analyze the relationship between the number of investors (Individuals) in variable income, comparing it with the variation in the basic interest rate (Selic) during the period between 2016 and 2020, assuming that there is a relationship inversely proportional to the variation of the Selic rate with the number of investors (individuals) on the Stock Exchange. That is, as the Selic rate is reduced, making investment in fixed income less attractive, the number of Stock Exchange users increases in the search for better returns on invested capital. The data necessary for carrying out the survey was obtained exclusively from B3 through contact made by email. The historical series of the monthly values of the Selic rate were extracted directly from the official website of the Central Bank (BACEN), corroborated by information contained in the Brazilian Association of Entities of the Financial and Capital Markets (ANBIMA), Brasil, Bolsa e Balcão (B3 S.A.) and the Brazilian Institute of Geography and Statistics (IBGE). The results show negative variations in the Selic rate since the beginning of the period, reaching a minimum of 1.90%; on average, a reduction of 80.02%. Inversely proportional, the average number of investors in the period showed a constant increase, from 558,034 investors in 2016 to 2,690,799 in 2020, a percentage increase of 382.19%. There was an increase of 219.55% in the volume of capital transacted, from 111.28 billion in 2016 to 355.60 billion reais in 2020, considering annual average values. The results confirm the initial assumption that the number of investors in variable income is inversely proportional to the variation in the basic interest rate (Selic). DOI: https://doi.org/10.56238/tfisdwv1-094